Prognostic Factors of Patency Loss of Arteriovenous Fistula After Percutaneous Transluminal Angioplasty - Srivachirawat, Peeranat; Lelamali, Kumtorn; Puavilai, Thitiya (Journal of the Nephrology Society of Thailand, 2024)
Introduction: Arteriovenous fistula (AVF) is recommended as 1st choice of vascular access for hemodialysis (HD). Percutaneous transluminal angioplasty (PTA) helps increase the patency of AVF, which enhances HD adequacy. However, a slow decline in blood flow rate over time after PTA is common. The present study examined factors associated with patency loss at 6 months after PTA. Method: This is a single-center prospective cohort study of 54 HD patients using AVF as dialysis access. Demographic data and characteristics of AVF were collected at baseline. The changes in blood flow rates after PTA were recorded immediately and at 3- and 6-month after the procedure. Factors associated with patency loss at 6 months after PTA were evaluated. Results: The average age of AVF was 77.1 ± 68.4 months. Sixty-three percent of the fistula were in the upper arm. Central vein stenosis was present in 15.3%. Forty-six percent had previous interventions to the fistula. The most common type of intervention was plain balloon angioplasty (90.7%). The access blood flow rate (ABF) rate improved significantly immediately after the PTA. However, a slow but significant decline in ABF rate was observed at 3 and 6 months. The patency rates of the fistula at 3 and 6 months were 94.4% and 75.9 %, respectively. Independent predictors for patency loss at 6 months were ABF <500 ml/min immediately after the procedure, multiple stenotic lesions, and higher PTH level. Higher hemoglobin and lower ABF rate immediately after the PTA were independently correlated with >25% decline in the ABF at follow-up Conclusion: Low ABF rate immediately after PTA, higher number of stenotic lesions, and higher PTH level predicted patency loss of AVF after PTA. These findings could help identify patients at high risk of AVF failure who might benefit from close monitoring.